NEUROSAINS KOGNITIF DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR (COGNITIVE NEUROSCIENCE OF MATHEMATICS EDUCATION IN ELEMENTARY SCHOOL) - Dessy Noor Ariani, Asep Supena (Jurnal THEOREMS (The Original Research of Mathematics), 2019)
ABSTRAKArtikel ini bertujuan untuk mendeskripsikan tahapan perkembangan kognisi numeric pada manusia dari bayi hingga sekolah menengah; bagaimana peran otak dalam pembelajaran matematika; hubungan neurosains kognitif dengan pendidikan matematika; karakteristik kognitif dengan perkembangan dan kognisi atypical pada siswa; dan intervensi dalam peningkatan kognisi matematika pada siswa sekolah dasar. Adapun saran penulis untuk penelitian yang lebih lanjut adalah berupa kolaborasi antara ilmuwan dan pendidik profesional yang relevan dengan bidang pembelajaran matematika  terutama pembelajaran matematika di sekolah dasar untuk menjanjikan kemajuan lebih lanjut dalam pemahaman tidak hanya kognisi matematika, tetapi juga peningkatan kognisi matematika pada siswa sekolah dasar, dengan implikasi jangka pendek dan jangka panjang yang bermanfaat untuk generasi masa depan.Kata kunci:matematika, neurosains kognitif, sekolah dasar.ABSTRACTThis article aims to describe the development of numerical cognitive development in humans from infants to secondary schools; what the role of the brain in mathematics learning is; the relationship of cognitive neuroscience with mathematics education; cognitive characteristics with atypical development and cognition in students; and intervention to improve mathematical cognition in elementary school students. Related to the author's suggestion for further research is collaboration between researchers and professional educators that relevant to the field of mathematics learning especially mathematics learning in elementary schools to encourage further progress in understanding not only mathematics, but also increasing knowledge about mathematics in elementary schools, and  short- and long-term impact on the education of future generationsKeywords:cognitive neuroscience, elementary school, mathematics.